2012
DOI: 10.1029/2011ja017118
|View full text |Cite
|
Sign up to set email alerts
|

Atypical nighttime spread‐F structure observed near the southern crest of the ionospheric equatorial ionization anomaly

Abstract: An atypical nighttime spread‐F structure is observed on ionograms at or above the F2 trace, near the crest of the ionospheric equatorial ionization anomaly (EIA) region. This ionospheric atypical spread‐F phenomenon was observed using two closed spaced (∼115 km) ionospheric soundings stations located in Sao Jose dos Campos (23.21°S, 45.97°W) and Cachoeira Paulista (22.70°S, 45.01°W), Brazil, in a low‐latitude station (near the southern crest of the EIA region), during nighttime, low solar activity, and quiet g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Tsunoda [2008] and Narayanan et al [2012] suggested that ST can be usually regarded as a proxy for largescale wave-like irregularity structures, which should be associated with the large-scale MSTIDs in our case. More studies on ST can be found from previous publications [e.g., Tsunoda, 2008;Fagundes et al, 2012;Narayanan et al, 2012;Lynn et al, 2013]. Mixed spread F (MSF) traces (simultaneous range and frequency spreading) [Candido et al, 2011] appeared between 23:00 and 00:45 LT when the depleted front "3" gradually passed over the digisonde.…”
Section: 1002/2014ja020944mentioning
confidence: 99%
“…Tsunoda [2008] and Narayanan et al [2012] suggested that ST can be usually regarded as a proxy for largescale wave-like irregularity structures, which should be associated with the large-scale MSTIDs in our case. More studies on ST can be found from previous publications [e.g., Tsunoda, 2008;Fagundes et al, 2012;Narayanan et al, 2012;Lynn et al, 2013]. Mixed spread F (MSF) traces (simultaneous range and frequency spreading) [Candido et al, 2011] appeared between 23:00 and 00:45 LT when the depleted front "3" gradually passed over the digisonde.…”
Section: 1002/2014ja020944mentioning
confidence: 99%